The Effect of E-Wallet Application Use on Financial Management Efficiency in Small and Medium Enterprises (SMEs) in Umbulharjo District - Hironimus Ririn (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of the use of E-Wallet applications on the efficiency of financial management in Small and Medium Enterprises (SMEs) in Umbulharjo District. Efficiency in financial management is defined as an effort to optimize the use of financial resources to minimize waste, accelerate decision-making, and increase the competitiveness of SMEs in the market. The increasing adoption of digital payment systems has changed the way businesses manage their finances, with E-Wallet applications becoming a popular choice among SMEs. The research method used is quantitative with a survey approach, with research subjects being owners or managers of SMEs who actively use E-Wallet applications as a financial transaction tool. The sample was taken by purposive sampling of 100 respondents. The results of this study emphasize the importance of utilizing digital financial technology, especially E-Wallet, in supporting the efficiency of SME financial management in the digital era. The results show that the use of E-Wallet applications has a very significant effect on the efficiency of SME financial management partially. This is indicated by a value of 26.609 which is much greater than t (table) 1.984 and a significance value of <0.001 <0.05. The correlation coefficient (R) of 0.937 indicates a very strong relationship between e-wallet use and financial management efficiency. The coefficient of determination (R Square) of 0.878 indicates that 87.8% of the variation in financial management efficiency can be explained by e-wallet use, while the remaining 12.2% is influenced by other factors.